Development of Teaching Materials Based Learning Management System “Sifajargoro” to Foster Attitudes of Responsibility and Student Learning Outcomes in The Subjects of Civics Fifth Grade Elementary School Students - Anang Budiantara; Mustaji Mustaji; Raden Roro Nanik Setyowati (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
The background of this study is that the use of Google Classroom in elementary school spoon II Bojonegoro is considered less effective e. This study aims to determine: 1) the development process of teaching materials based on LMS "Sifajargoro"; 2) the feasibility of teaching materials in terms of practical aspects, valid and effective. This type of research is the ADDIE development mod l. The subjects of this study were sixth-grade students of State Elementary School Sudu II-Bojonegoro academic year 2021/2022, totaling 18 children. Data were collected through validation instruments, written tests, and questionnaires. The results obtained: 1) process of developing teaching materials based on LMS "Sifajargoro" using ADDIE development model through 5 stages, namely: analysis, design, development, implementation, and evaluation n. 2) LMS-based teaching materials product "Sifajargoro" is said to be suitable for use as a medium of learning in terms of 3 aspects, namely: the validity aspect obtained from the validation results with an average score of 84.21% included in the valid criteria, the effectiveness aspect in terms of test questions obtained the percentage of students who complete is 70%, so it is said to be effective, and the practical aspect in terms of the questionnaire and the overall average percentage result is 73.97%, so it is included in the practical criteria. So that from the results of development can significantly improve student learning outcomes.